THE EFFECT OF DIVIDEND POLICY AND MACROECONOMICS ON STOCK PRICES: (Empirical Study on Basic and Chemical Industry Sector Companies Listed on the Indonesia Stock Exchange 2016-2020 Period) - Elsha Theresya Simajuntak; Sutandijo (Transpublika Publisher, 2022)
This study analyzes the Effect of Dividend Policy and Macroeconomics on Stock Prices. Dividend Policy is calculated using the Dividend Payout Ratio (DPR), while Macroeconomics is proxied by inflation, interest rates, and exchange rates, and the Stock Price is measured by the closing price. The population in this study is all manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange in 2016-2020. The technique used in this study was purposive sampling with five criteria as consideration and 11 company samples with a five-year period were obtained, so that 55 observational data were obtained. Data analysis in this study used panel data regression with the help of windows Eviews-9. The results of this study can be seen simultaneously that the variables of DPR, inflation, interest rates, and exchange rates have a significant influence on stock prices. However, partially only the exchange rate variable has a significant influence on the stock price, while the DPR variable, inflation, and interest rate do not affect the stock price.